Pengaruh Pola Asuh Orang Tua Terhadap Kecerdasan Emosional Anak Usia Dini Usia 5-6 Tahun di Kober Kurnia Asih - Wahyuni, Yeni; Elnawati, Elnawati; Awal Maulana, Redi (PT. Alahyan Publisher Sukabumi, 2025)
This study aims to describe teachers' efforts in improving the character of cooperation in early childhood aged 5-6 years through traditional clogs games in Kober Miftahul Huda. The character of cooperation is one of the important aspects in children's social development that needs to be instilled from an early age to support the ability to interact and collaborate with others. This study uses the classroom action research method (PTK) which is carried out in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of the study were 15 children aged 5-6 years in Kober Miftahul Huda. Data was collected through observation, interviews, and documentation. Data analysis was carried out qualitatively and quantitatively using descriptive techniques to evaluate the improvement of the character of cooperation. The results of the study show that the application of traditional clogs games in a systematic and structured manner can improve the character of children's cooperation. Children are seen to be more able to work together in groups, help each other, respect the opinions of friends, and obey the rules of the game. The percentage of improvement in children's cooperative character reached 85% in the second cycle compared to 65% in the first cycle. This shows that the traditional clog game is effective in building the character of early childhood cooperation.